Antagonistic mechanism of Bacillus velezensis HX0039 as a biocontrol agent against Trichoderma virens -induced “Sanghuang” green mold - Zhang, Ying; Gao, Wenheng; Zhang, Hui; Sun, Tao; Yang, Huixiang; Liu, Yan; Han, Xiaoyang; Yin, Dengke; Xu, Weifang (Applied and environmental microbiology, 2025)
“Sanghuang” mushroom is a valuable edible and medicinal fungus. It provides numerous health benefits, including antitumor, anti-inflammatory, and immunity-enhancing properties. However, its growth is affected by green mold disease caused by Trichoderma, which severely hampers yield and quality. Conventional fungicide-based control methods have drawbacks like health and environmental risks, as well as the emergence of resistant pathogens. This study innovatively focuses on Bacillus velezensis HX0039, a strain proven to be safe for both “Sanghuang” mushrooms and mice. In vivo and in vitro experiments showed that HX0039 not only exhibits strong antifungal activity but also effectively prevents and controls the occurrence of “Sanghuang” green mold disease. Furthermore, the novelty of this research lies in its potential mechanism of action: HX0039 produces diverse metabolites like lipopeptides (especially iturin A), macrolactin A, and bacillibactin to exert its antagonistic activities. Therefore, this work demonstrates the great potential of B. velezensis HX0039 as an alternative to chemical fungicides in “Sanghuang” production.